Constraints and robustness considerations in the optimisation of springboard diving takeoff technique: a simulation study - Kong, P. W.; Yeadon, M. R.; King, M. A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study was to investigate the effects of imposing anatomical constraints and robustness requirements on the optimisation of springboard diving takeoff technique. A planar eight-segment model of a diver with torque generators together with a springboard model was used to optimise takeoff techniques for maximum rotational potential in the forward dive group by varying the activation timings of the torquegenerators. Optimisation 1 imposed no constraints or robustness requirements. Optimisation 2 imposed anatomical constraints. Optimisation 3 imposed anatomical constraints and a requirement of robustness to perturbations in activation timing. The results showed that imposing both anatomical constraints and robustness requirements have a substantial effect on optimum simulated performance.